Ekspresi Tajdid dalam Syarah Hadis: Kajian Historis atas Subul al-Salām karya al-Ṣanʿānī (w. 1182 H/1769 M) - Mukaromah, Kholila (ASILHA (Asosiasi Ilmu Hadis Indonesia), 2023)
Subul al-Salām by al-Ṣanʿānī represents a critique of sectarian fanaticism within Islamic jurisprudence, articulated through his commentary on hadith. This critique is closely linked to al-Ṣanʿānī’s concern over the decline of the Muslim ummah in the Arab region during the 11th–12th centuries AH, which in turn spurred the discourse of Islamic intellectual reform as a response. Through a historical inquiry, this study aims to explore the relationship between his commentary on Bulūgh al-Marām and the socio-cultural dynamics experienced by al-Ṣanʿānī. This research is based on library sources and employs a qualitative method. It addresses three key questions: a) In what ways can the tendency to disengage from rigid adherence to a particular school of law be identified as a defining characteristic of al-Ṣanʿānī’s hadith commentary in Subul al-Salām? b) What historical factors contributed to the emergence of this characteristic? c) How do these factors correlate with the transformation toward a new model of understanding hadith commentary? The findings of this study reveal that al-Ṣanʿānī employed a critical and corrective approach to interpreting hadith, often engaging with and reassessing views from various legal schools. There is a close connection between the paradigm of Ibn Taymiyyah, which had developed as a discourse of tajdīd in the Arab-Islamic world at the time, and al-Ṣanʿānī’s dissatisfaction with sectarian conflicts, particularly in his homeland, Yemen. Ultimately, Subul al-Salām is also associated with his decision to renounce the Zaydī madhhab and adopt a non-aligned stance, free from commitment to any single madhhab.